Targeted genome modifcation in protoplasts of a highly regenerable Siberian barley cultivar using RNA-guided Cas9 endonuclease - S. V. Gerasimova; A. M. Korotkova; C. Hertig; S. Hiekel; R. Hofe; N. Budhagatapalli; I. Otto; G. Hensel; V. K. Shumny; A. V. Kochetov; J. Kumlehn; E. K. Khlestkina (Вавиловский журнал генетики и селекции)
The modifcation of crop genomes employing functional components of the microbial CRISPR/Cas immune system is a rapidly developing area of applied research. Site-directed plant genome modifcation by this technology involves the construction of Cas endonuclease- and guide-RNA-encoding vectors, delivery of the plasmid DNA into plant cells, processing of the chosen genomic target site by the corresponding gene products and regeneration of plants from modifed cells. The utilization of this technology in local breeding programs is mainly limited by the typically strong genotype dependence of gene transfer and in vitro regeneration procedures, which holds particularly true in cereals. In the present study, an evaluation of in vitro regeneration efciency of immature embryos of ten Siberian barley cultivars revealed that only one of these is on a par with the experimental standard cultivar Golden Promise. This cultivar, namely cv. Aley, was consequently chosen for further experiments on site-directed mutagenesis in leaf mesophyll protoplasts. Two genes controlling hulled vs naked (Nud) and two-rowed vs six-rowed barley (Vrs1) were used as targets to be modifed via polyethyleneglycol-mediated cellular uptake of guide-RNA/Cas9-encoding plasmid DNA. Deep-sequencing of amplicons obtained from protoplast genomic DNA revealed that 6 to 22 percent of the target sites were mutated. The detected modifcations comprised deletions in all three target sites and of various sizes, whereas insertions were observed in only one of the target genes (Vrs1) and were confned to the size of 1 nucleotide. This study demonstrates the possibility of site-directed genome modifcation in Siberian barley. Further steps in technology advancement will require the development of protocols with reduced genotype dependence in terms of both the gene transfer to totipotent cells and the subsequent plant regeneration originating from such cells.